Psychometric properties of a Mandarin version of the tinnitus questionnaire. (2nd June 2016) - Meng, Zhaoli; Chen, Zhenxi; Xu, Ke; Li, Gang; Tao, Yong; Kwong, Joey Sum-Wing
Abstract: Objective : To develop a Mandarin version of the tinnitus questionnaire (MTQ) and determine the reliability and validity, and to assess whether it could be used clinically in the Chinese population. Design : The MTQ, short-form (36) health survey, hospital anxiety and depression scale, Mandarin (Chinese) tinnitus handicap inventory, and visual analogue scale were completed by the participants. Study sample : We included 192 adults seeking treatment for primary or secondary tinnitus. Results : Five factors, namely, emotional distress, auditory perceptual difficulties, cognitive distress, sleep disturbance, and intrusiveness, were extracted from the MTQ. Thirty-seven items were included. The MTQ had high test-retest reliability (Spearman correlation coefficients: 0.87–1.00). The MTQ and its subscales had good internal consistency and reliability (total α = 0.93, subscales α = 0.71–0.86). A single measure of severity can be acquired by summing the five subscale scores. The MTQ was significantly correlated with psychological distress and tinnitus-related handicap. Conclusion : Our results demonstrated that the MTQ is a reliable and valid measure of tinnitus-related psychopathological symptoms and could be used clinically to evaluate tinnitus-related psychological problems. Questionnaires designed to explore tinnitus-related depression and other symptoms not covered by the scope of the MTQ are needed.